Penerapan Sanitasi Produksi Kue Pia Di Gorontalo - Linda Ishak; Jenny E.A. Kandou; Thelma D.J. Tuju; Tineke M. Langi (Universitas Sam Ratulangi, 2015)
ABSTRACT Pia cake is one of the food products of Gorontalo that have been produced by some home industry. In relation to food security that ensures that the food consumed does not contain hazardous materials that safe for consumption, so that need for oversight and implementation of good sanitation systems at pia produscing. This study aimed to evaluate the level of implementation of sanitation in UKM at Gorontalo. In this study is expected to provide information on the importance of implementing sanitation at UKM Pia manufacture in Gorontalo and provide information to the government in Gorontalo through relevant agencies about the principles of sanitation at UKM Pia in Gorontalo. The study used survey method, which takes primary data from field observations through interviews with the questionnaire guide. From the research data showed that in all UKM do not use a hat, gloves, masks, and aprons. While all employees in four UKM use the clothes clean, tidy and wash hands, to cookware and clean container. The processing is done, all UKM are still using the traditional method and storage of product on all UKM in hygienic circumstances. Keywords : pia, UKM, sanitary